Criminological Study on Criminal Activities Human Trafficking in the Nusa Tenggara Timur Region (NTT), Indonesia - Susanti, Vinita; Kosandi, Meidi; Imam Subono, Nur; Kartini, Evida (International Journal of Criminology and Sociology, 2022)
The rise of trafficking of women and children in the Nusa Tenggara Timur region, Indonesia. Research method, descriptive qualitative, consisting of primary data obtained through field studies using interview techniques, secondary data from literature. The results research of criminological on human trafficking are transnational crimes that have come to the attention of countries in the world. This crime is caused by the factors of poverty, low education, difficult employment opportunities, culture in society. According to human trafficking data from 2012 to 2016 there were 643 cases, consisting of 263 cases of labor, 310 cases of sexual abuse, 65 cases of default and 5 cases of selling babies. And as many as 754 victims, consisting of 418 adult women, 218 girls, 115 adult men and 3 boys. This prevention must begin with the inculcation of moral values and character in children, where this task is carried out by families such as parents at home and teachers at school. The Indonesian National Police as a guardian of security and order in society can make efforts to instill awareness about the dangers of crime in human trafficking.